Determining of expidience use of dry basil leaves in the technology of sour milk paste - Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana; Yatsenko, Olga; Mykhalevych, Artur; Kushil, Anna; Panchenko, Alexandra; Skyibida, Valeriya (My University, 2017)
The calculation o f the degree o f maintenance o f daily human needs in certain phenolic compounds with P-vitamin activity was estimated at the use of 100 g of sour milk paste (according to the formulations developed, the dose of the extract - 10 %). Consumption o f sour milk paste with an extract o f basil will ensure daily need for routine by 11.0 %, tannin - by 0.7 %, catechin - by 1.9 %.
Keywords: базилік; базилик; basil; кисломолочні пасти; кисломолочные пасты; sour milk paste; кафедра технології молока і молочних продуктів